A flow-through aqueous standard generation system for thin film microextraction investigations of UV filters and biocides partitioning to different environmental compartments. (November 2017) - Ahmadi, Fardin; Sparham, Chris; Pawliszyn, Janusz
Abstract: In this paper problems associated with preparation of aqueous standard of highly hydrophobic compounds such as partial precipitation, being lost on the surfaces, low solubility in water and limited sample volume for accurate determination of their distribution coefficients are addressed. The following work presents two approaches that utilize blade thin film microextraction (TFME) to investigate partitioning of UV filters and biocides to humic acid (dissolved organic carbon) and sediment. A steady-state concentration of target analytes in water was generated using a flow-through aqueous standard generation (ASG) system. Dialysis membranes, a polytetrafluoroethylene permeation tube, and a frit porous (0.5 μm) coated by epoxy glue were basic elements used for preparation of the ASG system. In the currently presented study, negligible depletion TFME using hydrophilic-lipophilic balance (HLB) and octadecyl silica-based (C18) sorbents was employed towards the attainment of free concentration values of target analytes in the studied matrices. Thin film geometry provided a large volume of extraction phase, which improved the sensitivity of the method towards highly matrix-bound analytes. Extractions were performed in the equilibrium regime so as to prevent matrix effects and with aims to reach maximum method sensitivity for all analytes under study. Partitioning of analytes on dissolved organic carbon (DOC) was investigated in ASG to facilitate large sample volume conditions. Binding percentages and DOC distribution coefficients (Log KDOC ) ranged from 20 to 98% and 3.71–6.72, respectively. Furthermore, sediment-water partition coefficients (Kd ), organic-carbon normalized partition coefficients (Log KOC ), and DOC distribution coefficients (Log KDOC ) were investigated in slurry sediment, and ranged from 33 to 2860, 3.31–5.24 and 4.52–5.75 Lkg -1, respectively. The obtained results demonstrated that investigations utilizing ASG and TFME can yield reliable binding information for compounds with high log KOW values. This information is useful for study of fate, transport, and ecotoxicological effects of UV filters and biocides in aquatic environment. Graphical abstract: Highlights: Steady state concentration of UV filters and biocides were generated. TFME was used to study their partitioning on DOC and sediment. Hydrophobic compounds show high affinity for DOC and bed sediment. Abstract : Negligible depletion TFME was used to accurately measure free concentrations of UV filters and biocides in humic aid and sediment. In this study, partition coefficients of target analytes between dissolved organic carbon (DOC), bed sediment, and water were determined. Hydrophobic compounds showed high affinity toward dissolved organic carbon (DOC) and bed sediment.